2020
DOI: 10.1039/d0an00440e
|View full text |Cite
|
Sign up to set email alerts
|

Driving force to detect Alzheimer's disease biomarkers: application of a thioflavine T@Er-MOF ratiometric fluorescent sensor for smart detection of presenilin 1, amyloid β-protein and acetylcholine

Abstract: ThT@Er-MOF has been successfully applied in highly sensitive detection of three main Alzheimer Disease biomarkers through three different low cost and facile detection strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 87 publications
0
21
0
Order By: Relevance
“…The ratiometric fluorescence sensor ThT@Er-MOF was able to detect the aforementioned AD biomarkers. 200 In the detection of presenilin 1, the spilled DNA strategy employed in the labelfree recognition of SSODN (part of the presenilin 1 gene) where fluorescence of ThT was enhanced due to the hydrogenbonding interactions between DNA and the MOF network. In the case of Aβ detection, it was observed that ThT has a special affinity for Aβ and displayed a brilliant characteristic fluorescence band (Figure 68).…”
Section: Sensing Of Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations
“…The ratiometric fluorescence sensor ThT@Er-MOF was able to detect the aforementioned AD biomarkers. 200 In the detection of presenilin 1, the spilled DNA strategy employed in the labelfree recognition of SSODN (part of the presenilin 1 gene) where fluorescence of ThT was enhanced due to the hydrogenbonding interactions between DNA and the MOF network. In the case of Aβ detection, it was observed that ThT has a special affinity for Aβ and displayed a brilliant characteristic fluorescence band (Figure 68).…”
Section: Sensing Of Biomarkersmentioning
confidence: 99%
“…In this regard, Ding and co-workers used solvothermal and facile ultrasonic method to prepare novel MOF [Er­(L)­(DMF) 1.27 ] n (Er-MOF) where fluorescent dye thioflavine T (ThT) was incorporated through postsynthetic modification of Er-MOF. The ratiometric fluorescence sensor ThT@Er-MOF was able to detect the aforementioned AD biomarkers . In the detection of presenilin 1, the spilled DNA strategy employed in the label-free recognition of SSODN (part of the presenilin 1 gene) where fluorescence of ThT was enhanced due to the hydrogen-bonding interactions between DNA and the MOF network.…”
Section: Ratiometric Sensing Application Of Mofmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the detection of fluorescence and colorimetric signals, the recognition of biomarkers would lead to changes in optical intensity or peak shifts in reflection spectra. 15,[22][23][24] Thus, optical sensors are MR compatible, immune to electromagnetic interference, and have lower signal drifts in continuous monitoring. When the optical sensors are combined with optical fibers, remote and deep brain sensing can also be achieved.…”
Section: Progress and Potentialmentioning
confidence: 99%
“…( Nakamura, Kaneko et al, 2018 ; Laís Canniatti, Isabella et al, 2019 ) In blood, the physiological concentrations of Aβ is several picograms per milliliter. To date, a great deal of sensing techniques has been performed to detect Aβ protein, including ELISA( Linan, Son et al, 2016 ), ion mobility-mass spectrometry (IM-MS)( Obata, Murakami et al, 2020 ), colorimetric biosensor( Xi, Shuangling et al, 2021 ), electrochemical( Carneiro, Loureiro et al, 2017 ), fluorescence( Lee, Park et al, 2019 ; Wang, Du et al, 2020 ; Wen-Kai, Liu et al, 2021 ), surface-enhanced Raman spectroscopy( Yang, Hwang et al, 2019 ), and photoelectrochemical (PEC) immunosensors( Wang, Fan et al, 2018 ). Among them, the PEC biosensor is an innovative and attractive analytical technique for quantitative study in the biological analysis due to its intrinsic merits such as label-free, high signal-to-noise ratio, rapid response, and is more readily miniaturized.…”
Section: Introductionmentioning
confidence: 99%